Standing at the threshold : working through liminality in the composition and rhetoric TAship - Macauley, William J.; Anglesey, Leslie R.; Edwards, Brady (Professor of English); Lambrecht, Kathryn M., 1988-; Lovas, Phillip (Utah State University Press, 2021)
"Articulates identity and role dissonances experienced by composition and rhetoric teaching assistants and reimagines the TAship within a larger professional development process. Current researchers and scholars have not fully explored the liminality of the profession's traditional path to credentialing"--Provided by publisher
Keywords: Graduate teaching assistants.; English language -- Rhetoric -- Study and teaching (Higher); Academic writing -- Study and teaching.; Assistants d'enseignement.; Écriture savante -- Étude et enseignement.; Higher.; EDUCATION.; Study & Teaching.; Academic writing -- Study and teaching; Graduate teaching assistants; Electronic books.